Optimizing antimicrobial therapy in urinary tract infections: A focus on urine culture and sensitivity testing - Alkhawaldeh, Rama; Abu Farha, Rana; Abu Hammour, Khawla; Alefishat, Eman (Frontiers in Pharmacology, 2022)
Objectives: This cross-sectional study was conducted at Jordan university hospital to evaluate the impact of microbial culture data and sensitivity results on optimizing UTI treatment. Methods: All positive urine cultures requested for adult patients (≥18 years) admitted to Jordan University Hospital (JUH) within the period from January 2019–July 2021 were evaluated. The antibiotics prescribed before and after culture data and sensitivity results were compared to evaluate the impact of these diagnostic measures on optimizing UTI treatment. Results: During the study period, 2400 urine cultures revealed positive results. Among those patients, 1,600 (66.7%) were discharged before the availability of culture results and excluded. Of the remaining 800 patients, 701 patients (87.6%) received empiric treatment. After culture and sensitivity results were available, overall, 84 (10.5%) patients had optimization (improvement) in their UTI management after culture results were known, while 6 (0.8%) patients had a worsening in their treatments. Based on the culture results, we found that only 12.4% of patients were appropriately treated before and after the culture results. Moreover, our results revealed that 31.9% were inappropriately treated for their UTIs before and after culture results. Conclusion: This study revealed an alarmingly high rate of inappropriate treatment of UTIs despite the availability of urine culture and sensitivity data, and that culture results were not used to optimize treatment strategies for UTI. This practice can potentially result in poor health-related outcomes and adversely affects efforts to battle AMR. Multifaceted strategies must be implemented to help clinicians follow the best current evidence and current guidelines in their selection of antibiotics for the management of UTIs.